Pendampingan Belajar Bahasa Inggris Melalui Kegiatan English Class Bagi Siswa MAN 2 Situbondo - Musdalifah Musdalifah; Nazilul Umami; Mega Selviana Dewi (Jurnal Multidisiplin Ibrahimy, 2023)
English is a language that must be master by learners. One of the important components in learning English is mastering vocabulary well. In addition, the right method is also needed to be able to develop an English skill, these are 4 skills that need to be developed, namely listening, reading, writing and speaking. In this case, the students of MAN 2 Situbondo learn together by "English Class" with the guidance of tutors from the students of English education study program, Ibrahimy University. English learning activities are carried out using the collaborative learning method which can help the students to be easier for learning English in the school environment, especially in the field of communication. In addition, the students also give a positive response by learning English together with their friends into doing a conversation and also perform mini drama. It also enhance the students motivation and being more confidence in learning English.